Fire Station, Dawson, Y. T. 1901 - Howard, Mart Albert, 1855-1926 (Manuscripts, Archives, and Special Collections, Washington State University Libraries: https://libraries.wsu.edu/masc, 1901)
1 Lantern Slide: b&w; 10 x 8 cm. Fire Station in Dawson, Yukon Territory.